2000
DOI: 10.1086/321211
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the Gene for Connexin 30.3 in a Family with Erythrokeratodermia Variabilis

Abstract: Erythrokeratodermia variabilis (EKV) is an autosomal dominant keratinization disorder characterized by migratory erythematous lesions and fixed keratotic plaques. All families with EKV show mapping to chromosome 1p34-p35, and mutations in the gene for connexin 31 (Cx31) have been reported in some but not all families. We studied eight affected and three healthy subjects in an Israeli family, of Kurdish origin, with EKV. After having mapped the disorder to chromosome 1p34-p35, we found no mutations in the genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 23 publications
2
83
0
1
Order By: Relevance
“…1 Erythrokeratodermas can be associated with sensorineural deafness and are caused by mutations in the gap junction proteins connexin 30.3 and 31. 2,3 Keratitis-ichthyosis-deafness ⁄hystrix-like ichthyosis-deafness syndrome is caused by mutations in GJB2 (connexin 26) and should also be grouped with the erythrokeratodermas. 4-6 Cases have been described without mutations in any of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Erythrokeratodermas can be associated with sensorineural deafness and are caused by mutations in the gap junction proteins connexin 30.3 and 31. 2,3 Keratitis-ichthyosis-deafness ⁄hystrix-like ichthyosis-deafness syndrome is caused by mutations in GJB2 (connexin 26) and should also be grouped with the erythrokeratodermas. 4-6 Cases have been described without mutations in any of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Four genes causing deafness (GJB1 (Cx32), GJB2 (Cx26), GJB3 (Cx31) and GJB6 (Cx30)) encode connexin proteins (http://www.iro.es/deafness) and distinct dominant mutations in three of these genes (GJB3, GJB2 and GJB6) are involved in skin diseases (reviewed in Kelsell et al, 2001 andRichard et al, 2000). Recently a mutation (F137L) in GJB4 (MIM# 605425) has been identified in affected members of a family with erythrokeratodermia variabilis (EKV; MIM#1 33200) (Macari et al, 2000) but the role of GJB4 in skin disorders has to be confirmed with the identification of additional EKV families with GJB4 mutations. Furthermore it is unknown whether, as in other epidermal disease-associated connexins, GJB4 mutations also result in hearing impairment.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Autosomal dominant EKV has been mapped to a single genetic locus on human chromosome 1p34-p35.1 harbouring a cluster of four connexin genes encoding the gap junction proteins Cx30.3 (GJB4), Cx31 (GJB3), Cx31.1 (GJB5) and Cx37 (GJA4). [7][8][9] In the majority of patients, EKV is caused by heterozygous missense mutations in two different connexin genes, GJB3 and GJB4. 4,8,10 Both genes are expressed in the upper spinous and granular layers of the epidermis and are thought to take part in the intercellular communication of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In the majority of patients, EKV is caused by heterozygous missense mutations in two different connexin genes, GJB3 and GJB4. 4,8,10 Both genes are expressed in the upper spinous and granular layers of the epidermis and are thought to take part in the intercellular communication of keratinocytes. 11,12 A small number of EKV patients, however, does not carry pathogenic connexin gene mutations and the molecular basis of the disorder in these patients still remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation